Governing Fear. From the Modern Dominance of Passions to Security Policies and Risk Management in the Global Era - Lanzillo, Maria Laura (Governare la paura. Journal of interdisciplinary studies, 2009)
Governing Fear. From the Modern Dominance of Passions to Security Policies and Risk Management in the Global Era.